2020
DOI: 10.1101/2020.05.06.080440
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coding and regulatory variants affect serum protein levels and common disease

Abstract: Circulating proteins are prognostic for human outcomes including cancer, heart failure, brain trauma and brain amyloid plaque burden. A deep serum proteome survey recently revealed close associations of serum protein networks and common diseases. The present study reveals unprecedented number of individual serum proteins that overlap genetic signatures of diseases emanating from different tissues of the body. Here, 55,932 low-frequency and common exome-array variants were compared with 4782 protein measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 70 publications
(119 reference statements)
0
17
0
Order By: Relevance
“…Availability of a large number of proteins or protein complexes in the SOMAScan platform as well as large sample size that almost tripled the number of cis-pGenes, i.e. genes that with at least one identified cis-pQTL, compared to studies conducted in the past 16,17 , and we successfully replicated over 92% (761/820) of the previously identified cis-pGenes. Further, analysis of data from both European American (EA) and African American (AA) samples allowed us to understand consistent genetic regulation of proteins across ethnic groups and better characterize sets of causal pQTLs through bi-ethnic fine-mapping analysis.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Availability of a large number of proteins or protein complexes in the SOMAScan platform as well as large sample size that almost tripled the number of cis-pGenes, i.e. genes that with at least one identified cis-pQTL, compared to studies conducted in the past 16,17 , and we successfully replicated over 92% (761/820) of the previously identified cis-pGenes. Further, analysis of data from both European American (EA) and African American (AA) samples allowed us to understand consistent genetic regulation of proteins across ethnic groups and better characterize sets of causal pQTLs through bi-ethnic fine-mapping analysis.…”
Section: Discussionmentioning
confidence: 58%
“…1b). Compared to plasma pQTL studies conducted in the past in European ancestry sample 16,17 , we tripled the number of cis-pGenes, i.e. genes that with at least one identified cis-pQTL, 17,18 and we successfully replicated over 92% (761/820) of previously identified ones (Supplementary Table 4).…”
Section: Identification Of Cis-pqtls Across European and African Amermentioning
confidence: 95%
See 1 more Smart Citation
“…The ABO signal (rs8176719-TC) overlaps several genes. We explored proteome-wide associations in three separate proteomic datasets 15,18,38 . Aside from the ABO protein, the ABO SNP rs8176719-TC showed the strongest association (Sun et al: p = 6.03 × 10 −258 , Emilsson et al: p = 1.00 × 10 −307 , Suhre et al: p = 1.27 × 10 −75 ) with higher plasma concentrations of soluble CD209 in all three datasets (associations from two datasets illustrated in Figure 3 , and associations from all three datasets tabulated in Table S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…A list of pGWAS studies was originally published by Suhre et al [74] and updated in their online web resource. Two of the most comprehensive studies used the SomaLogic platform and have identified 5553 exome array variants affecting 1931 proteins in 5457 individuals [83] and 1927 genomewide variants affecting 1478 proteins in 3301 individuals [82•]. We recently expanded the genetic discovery for a subset of 179 proteins from the SomaLogic platform, including 45 proteins with no previously described pQTLs, in 10,708 individuals [85].…”
Section: Beyond Prediction: Integration Of Genomics and Proteomics Tomentioning
confidence: 99%